Modelo descriptivo para mejorar la habitabilidad del territorio autoconstruido en América Latina y el Caribe (2022)
In Latin American and Caribbean countries, self-built or informal settlements are one of the main problems, where it is evident that their habitability indexes are not optimal, in addition, regarding urbanization processes, an unplanned growth is observed and currently it has not been possible to respond to unsustainable urban trends, where changes and problems are generated in the persistent patterns of inequality, inequity and exclusion (Torres & Guerrero, 2008; Villatoro et al, 2017).